Implementasi Pendidikan Seksualitas PAUD Berbasis Agama: Implementation of Religion-Based Early Childhood Sexuality Education - Binantari, Dhiana; Kurniawati Sugiyo Pranoto, Yuli; Diana (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
This article reviews the literature on the Implementation of Faith-Based Sexuality Education focusing on Early Childhood Education (ECED) schools in Indonesia. This systematic literature review (hereafter SLR) involved searching, screening and synthesizing articles on faith-based sexuality education published in the last ten years (2014-2024) from electronic databases namely SCOPUS, Google Scholar. The findings of this review identified 15 relevant articles and revealed that most of the relevant studies were conducted qualitatively with a focus on the implementation of faith-based sexuality education. In addition, the researcher applied the concept of sexuality education from various specific religions whose research topic mapping has been widely studied but received less attention, such as whether faith-based sexuality education is successful in the long run, whether it is accepted by various religious communities, and how it is best for early childhood education. In addition, the researcher used several conceptualizations of sexuality education involving educators, institutions, government agencies. This study suggests that further qualitative research is needed to understand the importance of implementing sexuality education in faith-based institutions by involving government agencies and educators to find out the forms of practices used in the delivery of sexuality education by educators.   ABSTRAK  Abstrak. Artikel ini mengulas literatur tentang Implementasi Pendidikan Seksualitas Berbasis Agama yang berfokus pada sekolah Pendidikan Anak Usia Dini (PAUD) di Indonesia. Tinjauan literatur sistematis (selanjutnya disebut SLR) ini meliputi pencarian, penyaringan, dan sintesis artikel-artikel pendidikan seksualitas berbasis agama yang diterbitkan sepuluh tahun terakhir (2014-2024) dari database elektronik yaitu SCOPUS, Google Scholar. Temuan tinjauan ini mengidentifikasi 15 artikel yang relevan dan mengungkapkan bahwa sebagian besar penelitian yang relevan dilakukan secara kualitatif dengan fokus pada Implementasi pendidikan seksualitas berbasis agama. Selain itu, peneliti menerapkan konsep pendidikan seksualitas dari berbagai agama tertentu yang pemetaan topik penelitiannya sudah banyak dipelajari namun kurang mendapat perhatian, seperti apakah pendidikan seksualitas berbasis agama berhasil dalam jangka panjang, apakah diterima oleh berbagai pihak. komunitas agama, dan bagaimana cara terbaik untuk pendidikan anak usia dini. Selain itu, peneliti menggunakan beberapa konseptualisasi pendidikan seksualitas dengan melibatkan pendidik, lembaga, instansi pemerintah. Penelitian ini menunjukkan bahwa diperlukan penelitian kualitatif lebih lanjut untuk memahami pentingnya penerapan pendidikan seksualitas di lembaga berbasis agama dengan melibatkan instansi pemerintah dan pendidik untuk mengetahui bentuk praktik yang digunakan dalam penyampaian pendidikan seksualitas oleh para pendidik